Intensified local grievances, enduring national control: the politics of land in the 2017 Kenyan elections. Issue 2 (3rd April 2019) - D'Arcy, Michelle; Nistotskaya, Marina
ABSTRACT: Constitutional provisions for devolution and land reform sought to address local land grievances and decentralize land administration in ways that would prevent conflict. The article argues that partial implementation of this agenda has intensified local grievances in a context of enduring national control over land administration. Local grievances have intensified as devolution has empowered majority communities and stoked their attachment to homelands, while the constitutional recognition of ancestral land rights has provided them with a legal basis for their claims. The failed decentralization of land administration has left national institutions as the focus of these claims. We examine whether these trends affected the use of land as a political resource and the rhetoric of land grievance during the 2017 elections. Using regression analysis, we find that titles were used patrimonially in the presidential elections, with titles targeted at Kikuyu minorities outside of their homelands. Our qualitative analysis suggests that the rhetoric of land grievances was limited in gubernatorial campaigns, suggesting that continued centralization in land administration retains the focus of land issues at the national level. Overall, our findings suggest that the partial implementation of the Constitution has exacerbated the conditions that led to land-based conflict in the past.